CYBERSECURITY RISKS IN FINANCIAL APPLICATIONS: IMPLICATIONS FOR INTERNAL CONTROL AND ASSURANCE - Rizkiawan; Siti Aisyah; Juwita Aprilia; Nuuridha Matiin (Universitas La Tansa Mashiro, 2026)
This study aims to analyze the impact of cybersecurity risks on the effectiveness of internal control and assurance functions in financial applications. Using a quantitative approach, data were collected from 87 respondents who are active users of financial applications through a structured questionnaire. Regression analysis was employed to examine the relationship between the independent variable (cybersecurity risks) and the dependent variables (internal control and assurance). Hypothesis testing results indicate that cybersecurity risks have a significant positive effect on the effectiveness of internal control and assurance (t = 7.84, p < 0.001). The coefficient of determination (R² = 0.62) shows that 62% of the variation in internal control and assurance effectiveness can be explained by cybersecurity risks. These findings highlight the necessity for organizations to strengthen risk mitigation strategies and integrate IT controls into financial systems to ensure reliability and resilience.